Pemetaan Jalur Evakuasi Bencana Gempabumi dan Tsunami Berbasis Network Analyst di Kawasan Perkotaan Lewoleba Provinsi Nusa Tenggara Timur - Tasya Meylinda Pattinasarany; Ferad Puturuhu; Adnan A.A. Botanri (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This research aims to map the path and access of earthquake and tsunami disaster evacuation achievements in the Lewoleba urban area, East Nusa Tenggara. This area is in a high risk zone, so effective evacuation planning is needed. The method used is a GIS-based Network Analyst that determines the fastest and closest evacuation route from the risk point to the shelter. The data used includes networks, risk points, shelters, and elevation data. The analysis is carried out by considering the distance, travel time, and topography. Research results show that there are still shelters that meet the safety criteria, and a number of areas have not yet reached the optimal evacuation route. Recommendations in the form of adding risk starting points and evaluating the location of shelters and evacuation routes are given as mitigation efforts. This research is expected to be the basis for planning spatial-based disaster evacuation routes in disaster-prone area